A new class of asymmetric turbo code for 3G systems - RAMASAMY, K; ALBALAKRISHNAN, B; SIDDIQI, M (2006)
In this paper, we propose a new asymmetric turbo encoder for 3G systems that performs well in both "water fall" and "error floor" regions. The Recursive Systematic Convolutional (RSC) encoder with generator polynomials (1, D-3+D-2+1/D-3+D+1), i.e. (13/11) in decimal and 3G interleaver are used for the typical Wideband Code-Divison Multiple Access (WCDMA) and Code-Divison Multiple Access 2000 (CDMA2000) turbo codes. The proposed asymmetric turbo code uses generator polynomials (1, D-3+D-2+1/D-3+D+1; D-3+D-2+1/D-3+1), i.e. (13/11;13/9) and a code-matched interleaver. The effect of interleaver in the proposed asymmetric turbo code is studied using weight distribution and simulation. The simulation results and performance bound for proposed asymmetric turbo code for the frame length, N = 400, code rate, r = 1/3 with Log-MAP decoder over additive white Gaussian noise (AWGN) channel are obtained and compared with the typical system. The performance tests are extended over both AWGN and Rayleigh fading channels for different frame size to verify the possibility of implementation of the proposed asymmetric turbo code. From the performance results, it is observed that the proposed asymmetric turbo code performs better than the typical system at both low and high SNR and it provides a coding gain of 0.5-0.8 dB. (c) 2005 Elsevier GrnbH. All rights reserved.